PENGEMBANGAN PERANGKAT PEMBELAJARAN DENGAN MODEL PBI MELALUI METODE GI PADA MATERI EKONOMI BISNIS KELAS X - Siti Nur Halimah; Elis Irmayanti; Efa Wahyu Prastyaningtyas (PROMOSI: Jurnal Program Studi Pendidikan Ekonomi, 2020)
The background of this research is that business economics learning at SMK PGRI 3 Kediri is still dominated by teacher-centered learning. This study uses a Research and Development (R&D) model with the subject of expert validation of learning devices. The objectives of this study are 1) To determine the steps for developing learning tools with the Problem Based Instruction (PBI) learning model through the Group Investigation (GI) method on Class X Business Economics Material, 2) To determine the feasibility of learning tools with a problem based learning model instruction (PBI) through the group investigation (GI) method on Class X Business Economics Material. The results of the development of this learning device are (1) The stages of development are carried out by testing the validation of learning device experts using the Thiagarajan 3D development model procedure (2)77% indicates that the learning device is declared feasible with revision, then in the second stage the validation of the learning device gets 93.5% results, which means that the learning device is declared very feasible or very valid and can be used for trials in class X students. Keywords: Problem Based Instruction (PBI), Group Investigation (GI), Business Economics.